Cell models for studying muscle insulin resistance - Pavlović, Kasja; Lalic, Nebojsa (Medicinski podmladak, 2021)
Type 2 diabetes is one of the most prevalent chronic diseases in the world today. Insulin resistance – a reduced responsiveness of tissues to insulin - is a hallmark of type 2 diabetes pathology. Skeletal muscle plays a pivotal role in glucose homeostasis - it is responsible for the majority of insulin-mediated glucose disposal and thus is one of the tissues most affected by insulin resistance.To study the molecular mechanisms of a disease, researchers often turn to cell models – they are cheap, easy to use, and exist in a controlled environment with few unknown variables. Cell models for exploring muscle insulin resistance are constructed using primary cell cultures or immortalised cell lines and treating them with fatty acids, high insulin or high glucose. The choice of cell culture, concentration and duration of the treatment and the methods for measuring insulin sensitivity in order to confirm the model are rarely discussed. Choosing an appropriate and physiologically relevant model for a particular topic of interest is required in order for the results to be reproducible, relevant and translatable to more complex biological systems. Cell models enable research that would otherwise be inaccessible but, especially when studying human disease, they do not serve a purpose if they are not in line with the biological reality.This review aims to summarise and critically evaluate the most commonly used cell models of muscle insulin resistance: the rationale for choosing these exact treatments and conditions, the protocols for constructing the models and the measurable outcomes used for confirming insulin resistance in the cells.
Keywords: insulin resistance; cell model; muscle; cell line; treatment; concentration